Cane-Scale Queuing System Modelling at PG Pandjie Situbondo - Purwaningsih, Isti; Effendi, Usman; Rizqi, Muhammad (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
Research was aimed to develop the cane-scale queuing system at PG Pandjie, Situbondo, and to find good solution to fix the waiting line problem. Based on this research the queuing model that used in cane scale is (M/M/1):( FIFO/∞/∞) with arrival rate (λ) 84 truck/hour, service rate (µ) 39 truck/hour, and average waiting time in the system is 7 hours and 3 minutes. To improve this system performance, there are 3 alternative, first alternative is to decrease the service time. Therefore, the service rate will increase to 45 trucks per hour. This alternative will decrease average waiting time in the system to 5 hours 45 minutes. Second alternative is to add a service facility. This alternative will decrease average waiting time to 47 minutes. Third alternative is combining the first alternative and second alternative. Average waiting time in the system decreases until 11 minutes if this alternative is implemented. Based on utility factor and probability, costumer must wait. The best alternative to solve the waiting line problem in cane scale station is third alternative. This is due to this alternative has utility factor that equal than 1 and the probability for costumer to wait is smaller than the other alternative.Keywords: cane-scale station queuing system, modelling, utility factor